CARA MEMATIKAN POHON RASAMALA SEBELUM PENEBANGAN DAN PENGARUHNYA TERHADAP SERANGAN KUMBANG AMBROSIA - Paimin Sukartana; Abdurahim Martawijaya (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
This experiment was designed to find out a proper method of killing rasamala trees (Altingia excelsa Noronha) before felling to improve the value of the wood. The methods in the testing include girdling, singed with blowtorch on the girdling section, and poisoned with 5% sodium arsenite solution or triclopyr 483.6 g/l or a mixture of triclopyr 100 with picloram 50 g/l. The chemical methods was conducted by pouring 5 ml of each chemical into each axed part of about 30 cm spacing which were made on the base of the tested trees. Poisoning with sodium arsenite was also done by brushing the solution on the girdled areas. The incidence of ambrosia beetle attacks was inspected to study the effect of the treatments on the susceptibility of the tested trees to the wood boring insects because this group of the pests may cause severe damage on the newly dead trees if improper treatment was carried out. The experiment concludes that :It seemed hard to kill rasamala trees by girdling even though the girdled section was singed with blowtorch.Poisoning with 5% sodium arsenite solution was effective if the chemical was brushed on the girdled section. Application of this method killed about 80% of the tested trees after six month period of treatment.Poisoning of rasamala trees with 483.6 g/l triclopyr of a mixture of triclopyr 100 with picloram 50 g/l through spacing axed cuts made on the base of tree was effective. The first formula killed about 80% of the trees after six months to one year. Application of the latter chemical showed better result because at the same treatment period this formula killed more trees, about 80 - 100% of the tested samples.In case of the ambrosia beetle infestation, the entire poisoned trees were more susceptible than that of the other treatments. Because the most attacks were mainly concentrated arround the treated areas, the damage is probably only meager in economic role.